Spin-photon interfaces in diamond and SIC systems - Mu, Zhao (Nanyang Technological University, 2022)
Color centers in wide bandgap materials that behave as ‘artificial atoms’ are promising candidates for quantum applications. The negatively charged nitrogen-vacancy (NV-) center in diamond is a benchmark platform for testing the quantum sensing, the quantum communication, and the quantum computation. However, the optical properties of the NV- center system are not yet perfect for the realization of the quantum network. Compared to the NV- center, there are many types of defects in diamond or hosts like silicon and silicon carbide (SiC) which exhibit superior optical properties. This thesis is devoted to studying two spin-photon interfaces including group IV defects in diamond and NCVSi- centers in SiC. Chapter 1 presents basic elements of the quantum network employing the quantum resources in the solid-state color centers systems. The latest progress in the quantum computation and the quantum network based on these systems are then presented. After that, the motivation of this study is introduced regarding the emerging challenges. Chapter 2 starts with introducing several experimental methodologies utilized for the optical and spin study of color centers. Then it describes the physical properties of diamond and SiC hosts along with molecular configurations of two kinds of defects. The recent progress on the optical and microwave manipulation of the group IV defects in diamond and defects (silicon-vacancy (VSi-), divacancy (VV0), and NCVSi- centers) in SiC are reviewed. Chapter 3 presents our study of the negatively charged germanium vacancy (GeV-) center in diamond. The GeV- centers in the diamond sample exhibit quenched emission upon resonant excitation but could be lightened up with an additional off-resonant excitation. We attribute this abnormal behavior to the presence of an extra dark. The competing dynamical process between a ‘dark’ state and a ‘bright’ state is further investigated and simulated with a three-level system. Chapter 4 presents our observation of the binary spectral jump behavior of Ge-related single-photon emitters in diamond. The optical properties of these emitters are investigated. Chapter 5 presents the study of NCVSi- centers in 4H-SiC. The fine orbital structure of the excited states and the zero-field splitting in the spin ground states are characterized by resonant laser excitation and microwave-assisted spin manipulation. The coherent manipulation of NCVSi- centers ensembles is realized upon resonant excitation. Meanwhile, single NCVSi- centers generations and their optical properties are reported. Chapter 6 begins by drawing conclusions on this thesis. After that, outlooks on several possible directions toward better spin-photon interfaces are presented.